(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The registrar department keeps the most vital work in an educational institution. Keeping a considerable amount of data and information over decades requires a huge storage or repository capacity and should be managed automatically without compromising data integrity and security. Thus, this research was conducted to ensure the efficiency and productivity in the Registrar Department of Bestlink College of the Philippines; processes, such as medical examination, enrollment process of incoming students and incoming students from Bestlink College of the Philippines (BCP) SHS, and graduation application, should be improved. This feasibility study utilized the qualitative method. To gather data, the researchers interviewed and surveyed therespondents. The researchers also observed inside the Registrar Department of BCP. The respondents were mainly the employees of this department. Teachers and students who deal with the employees of the registrar’s office were also included as respondents.These tools allowed the researchers to ascertain the progress achieved by the registration/records team as a result of the researchers’ suggestions for improvement and innovation. The results are indicators of customer and employee satisfaction and provide direction for future endeavors. Based on the observation, the medical examination should be mandatory for all students to avoid misleading information. Medical waivers will be given to all students. The waiver will have two copies, one copy for the registrar department and the remaining copy for the clinic. For incoming students, medical waivers will be given in the admission with the enrollment slip/step. For old students, medical waivers will be given in the registrar’s department before the medical examination. On the submission of requirements for incoming students, the record officers allow the student to write a promissory note for the follow-up requirements. The validity of the promissory will last until the end of 1st semester. However, the submission of pertinent documents is not implemented well. Thus, the researchers proposed that the registrar’s office should provide the students with a promissory form that lists the primary documents that should be submitted upon enrolling and a secondary document that should be submitted within 2 months. The recording officer will not sign the clearance of the students who will not comply. The graduation application form was filed on the first semester of 4th-year students. Hence, the students cannot make time to enroll in failed subjects because time is only limited for graduating students to comply with their failed/back subjects for the last semester. The researchers proposed to have verification on their 3rd year, 2nd semester. The rapid growth in the population of Bestlink and additional courses also led to overload work among the employees. The results of this study showed that such improvement is needed to enhance and promote the efficiency of the processes, including the workplace of the Registrar Department.